(untitled) (American Journal of Interdisciplinary Research and Development, 2022)
In this article, the results of the research carried out in the field of cultivation, storage and processing of rice crops using modern resource-saving technologies are written with an in-depth scientific analysis. Also, the article provides scientific conclusions and advice for production industries.